Simple and Easy DNA Mapping Method Using Peptide Nucleic Acid (PNA) Tagging - Kim, J.; Park, J. H.; Lee, S.; Shin, H. J. (AMER SCIENTIFIC PUBLISHERS, 2014)
In this paper, we introduce a simple and easy DNA mapping method using peptide nucleic acid (PNA) on glass cover-slips based on optical detection. PNA and glass cover-slips were used as easy tagging and stretching method, separately. The PNA can be invaded lambda (lambda) DNA at the sequences we wished to tag without any additional materials. Alexa-488 fluorophore-conjugated PNA was designed to invade at four sites (sequence: AAGAAGAA) of lambda DNA with robust and exact binding. Fluorophore tagged lambda DNA was stretched in electrical layer coated glass cover-slips. The lambda DNA was stretched as 9.2 um in length. It is approximately 60% of theoretical length of lambda DNA and sufficient length to promise optical resolution. The sites of desired sequence tagged by PNA were well detected in stretched lambda DNA.
Keywords: SINGLE-MOLECULE DETECTION; GEL-ELECTROPHORESIS